2022
DOI: 10.3390/diagnostics12040893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Nutritional Assessment Tools in Detecting Malnutrition and Sarcopenia among Cirrhotic Patients

Abstract: Malnutrition and sarcopenia are common complications of liver cirrhosis. This study compares the performance of different nutritional assessment techniques in detecting malnourished patients. Data from 156 patients with liver cirrhosis were collected. We assessed the nutritional status of these patients according to: Subjective Global Assessment (SGA); Royal Free Hospital-Nutritional Prioritizing Tool (RFH-NPT), skinfold thickness (TSF), mid-upper arm circumference (MUAC), mid-upper arm muscle circumference (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
8
0
5
Order By: Relevance
“…In patients with liver cirrhosis, although albumin levels are primarily influenced by hepatic synthetic function, it is also influenced by other factors such as decreased protein intake, increase of the catabolic state, increased vascular permeability, systemic inflammatory response, protein-losing enteropathy secondary to portal hypertension, and impaired immunity (38,(40)(41)(42)(43)(44)(45)(46)(47)(48). Additionally, Topan et al reported that low albumin levels were associated with malnutrition in patients with liver cirrhosis (49). Secondly, a previous study has shown that activated and differentiated CD4 + T lymphocytes are recruited to the inflamed liver and cause liver inflammation (50).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with liver cirrhosis, although albumin levels are primarily influenced by hepatic synthetic function, it is also influenced by other factors such as decreased protein intake, increase of the catabolic state, increased vascular permeability, systemic inflammatory response, protein-losing enteropathy secondary to portal hypertension, and impaired immunity (38,(40)(41)(42)(43)(44)(45)(46)(47)(48). Additionally, Topan et al reported that low albumin levels were associated with malnutrition in patients with liver cirrhosis (49). Secondly, a previous study has shown that activated and differentiated CD4 + T lymphocytes are recruited to the inflamed liver and cause liver inflammation (50).…”
Section: Discussionmentioning
confidence: 99%
“…Históricamente, la valoración global subjetiva (VGS) representaba el patrón oro de evaluación nutricional, hasta que, en las últimas guías de práctica clínica, se recomendó la aplicación del RFH-GA, por ser una herramienta específica para hepatopatía crónica, mientras que la VGS presentaba una baja correlación con otras mediciones objetivas de evaluación nutricional y subvaloraba la pérdida mus- cular en esta población. 3,[29][30][31] Al respecto, Gottschall halló una prevalencia de malnutrición del 84% con el RFH-GA (n = 56), mientras que Gunsar describió, con el mismo instrumento, 57,2% (n = 222). 12,32 En el presente trabajo, la prevalencia de malnutrición es del 42%, no hallándose antecedentes estadísticos en la población argentina.…”
Section: Discussionunclassified
“…Sarcopenia prevalence in patients with liver cirrhosis (LC) of different aetiologies (prevalence of cirrhotic NASH not specified) varies between 21.7% and 76% [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. In studies involving patients with LC of different aetiologies and with a prevalence of NASH/NAFLD ranging from 9.8% to 34.5%, sarcopenia prevalence varies from 19.8% to 48% [ 79 , 80 , 81 ].…”
Section: Sarcopeniamentioning
confidence: 99%